2021
DOI: 10.1016/j.gfs.2021.100498
|View full text |Cite
|
Sign up to set email alerts
|

Ground truthing the cost of achieving the EAT lancet recommended diets: Evidence from rural India

Abstract: In this paper, we quantify the divergence in the cost of current diets as compared to EAT Lancet recommendations at the subnational-level in India. We use primary data on food prices and household food purchases, and secondary data on food expenditures for a period of 12 months in 2018–19. The cost of the EAT Lancet dietary recommendations for rural India ranges between $3.00- $5.00 per person per day. In contrast, actual dietary intake at present is valued at around $1.00 per person per day. In order to get t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“… 19 A recent assessment of the cost of the EAT Lancet recommended diet would cost the equivalent of INR 260 per day per person (or INR 1300 per day per household). 20 Other studies focusing on behavior-change in rural-Indian households have also noted affordability as a key barrier to improving diets. 21 , 22 In addition, in Assam tea estates, food markets are only held on a weekly basis making the availability of fresh nutritious foods limited.…”
Section: Discussionmentioning
confidence: 99%
“… 19 A recent assessment of the cost of the EAT Lancet recommended diet would cost the equivalent of INR 260 per day per person (or INR 1300 per day per household). 20 Other studies focusing on behavior-change in rural-Indian households have also noted affordability as a key barrier to improving diets. 21 , 22 In addition, in Assam tea estates, food markets are only held on a weekly basis making the availability of fresh nutritious foods limited.…”
Section: Discussionmentioning
confidence: 99%
“…Countries with less wealth face even greater financial challenges to meeting healthy, sustainable dietary guidance. It was reported that the cost of the sustainable EAT-Lancet diet for rural India ranged between USD 3.00 and USD 5.00 per person per day in contrast to current dietary intake at a value of USD 1.00 per person per day [ 22 ]. The authors also noted challenges to achieving recommended diets are exacerbated by seasonal variations and volatility in food prices [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the cost of the sustainable EAT-Lancet diet for rural India ranged between USD 3.00 and USD 5.00 per person per day in contrast to current dietary intake at a value of USD 1.00 per person per day [ 22 ]. The authors also noted challenges to achieving recommended diets are exacerbated by seasonal variations and volatility in food prices [ 22 ]. The FAO stated that where countries have national food-based dietary guidelines, there is often a lack of policy coherence on how to ensure the affordability of those diets recommended for nutrition and health.…”
Section: Discussionmentioning
confidence: 99%
“…7 A study published in Global Food Security in March 2021 estimated that Indians eat a diet that costs roughly $1 (£0.73; €0.85) per day-roughly a fifth of the cost of the least expensive healthy diet recommended by the EAT-Lancet Commission. 8 The loss of jobs during the lockdown has cut household spending for millions of people, and a study published in Economia Politica showed that Indian women's dietary diversity declined during the lockdown compared with the same period in 2019, showing decreased consumption of meat, eggs, vegetables, and fruit. 9 But the biggest problem is the disrupted healthcare system.…”
Section: If Not Covid Then What?mentioning
confidence: 99%
“…Nutrition, for instance, could be a factor—over 77% of Indian households were consuming less food in 2020 (during the pandemic and lockdown) than before and food insecurity was higher among women, Muslims, Scheduled Castes, and people with lower education, according to a report by Azim Premji University based on a survey on 5000 workers across the various sectors 7. A study published in Global Food Security in March 2021 estimated that Indians eat a diet that costs roughly $1 (£0.73; €0.85) per day—roughly a fifth of the cost of the least expensive healthy diet recommended by the EAT-Lancet Commission 8…”
Section: If Not Covid Then What?mentioning
confidence: 99%